2000
DOI: 10.1021/ja002218r
|View full text |Cite
|
Sign up to set email alerts
|

Oxaluric Acid as the Major Product of Singlet Oxygen-Mediated Oxidation of 8-Oxo-7,8-dihydroguanine in DNA

Abstract: Oxidative reactions of DNA commonly result in base modifications. Among the four DNA bases, guanine is the most susceptible to oxidation, and one of its main oxidized compounds, namely 8-oxo-7,8-dihydroguanine (8-oxoGua), has been extensively studied in terms of formation, repair, and mutagenicity. However, the latter modified purine base is readily subjected to further oxidation reactions which have recently become a matter of interest. Emphasis was placed in this work on the identification of the final singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
133
1
5

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 133 publications
(147 citation statements)
references
References 34 publications
8
133
1
5
Order By: Relevance
“…Another argument that supports this hypothesis is that laser excitation of the radicals results in the formation of dehydroguanidinohydantoin lesions as the major product. The latter lesions slowly transform to the oxaluric acid lesions as reported earlier (43,44).…”
Section: Dynamics Of Guanine Lesion Formation-the Combination Of the supporting
confidence: 70%
“…Another argument that supports this hypothesis is that laser excitation of the radicals results in the formation of dehydroguanidinohydantoin lesions as the major product. The latter lesions slowly transform to the oxaluric acid lesions as reported earlier (43,44).…”
Section: Dynamics Of Guanine Lesion Formation-the Combination Of the supporting
confidence: 70%
“…Product 1 was therefore proposed to be oxidised Guanidinohydantoin, Gh ox , based on previous studies which indicated that this 290 compound, which has been shown to be unusually stable, was a main product of 8-oxoGua oxidation. 11 were about one third lower than for corresponding iron incubations.…”
Section: Apparatusmentioning
confidence: 59%
“…Sp, Iz and Oz were detected on oxidation of 8-oxodGuo by chemically induced 1 O 2 , 12 with Oxa detected on oxidation of single stranded oligomers 60 containing 8-oxodGuo. 11 Hydroxyl radical (•OH) oxidation of dG was found to generate Oz under reducing conditions, 13 however, for •OH oxidation induced by iron (II) ions, further oxidation of 8-oxoGua was expected to be prevented. 14 Photoirradiation produced Iz as the major product of DNA 65 oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…This excited species, which can be generated by an energy transfer mechanism (6,7), exhibits high reactivity and can be produced in biological systems (8,9). In mammalian cells, O 2 ( 1 ⌬ g ) can be generated during oxidative stress, and it is able to attack DNA, protein thiol groups, and membrane lipids (11)(12)(13)(14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%